TINJAUAN WAKTU DAN BIAYA MENGGUNAKAN METODE PERCEPATAN (CRASHING) DENGAN PENAMBAHAN JUMLAH TENAGA KERJA PADA PROYEK PEMBANGUNAN KANTOR KEJAKSAAN KOTA PONTIANAK KALIMANTAN BARAT: TINJAUAN WAKTU DAN BIAYA MENGGUNAKAN METODE PERCEPATAN (CRASHING) DENGAN PENAMBAHAN JUMLAH TENAGA KERJA PADA PROYEK PEMBANGUNAN KANTOR KEJAKSAAN KOTA PONTIANAK KALIMANTAN BARAT - Virgarif, Fahmi; nurharis, didik; Arena, Azza (Jurusan Teknik Sipil Polnep, 2022)
The District Attorney's Office is one of the government-owned buildings. This building has legal services such as legal consultation, ticketing, reports and complaints. To create a more comfortable and conducive public service atmosphere. The prosecutor's office was renovated by increasing the number of floors and building area and using reinforced concrete construction. Effective and efficient in construction projects is important, because there are a series of work mechanisms, each of which influences each other. An important thing that must be seen in a construction is cost, time, human resources, occupational health safety management system (SMK3) and project communication management. The calculation of crashing with the alternative of increasing the number of workers, the duration obtained is 2621 days with a normal duration of 3276 days, so the difference is 655 days. Calculation of crashing with the alternative of increasing the number of workers, obtained the number of workers by 25%, namely 368 people, with a normal workforce of 1471 people. The total cost for crashing is Rp. 8,983,027,796.81 with the normal cost of Rp. 8,800,156,476,89. So an additional fee of Rp. 183,031,862.95 was obtained. Normal direct costs are Rp.6,956,645,315.62 while normal indirect costs are Rp.1,843,511,161.27. The direct cost of crashing is Rp. 7,139,677,179 while the indirect cost of crashing is Rp. 1,843,511,161.27. With a total normal cost of Rp. 8,800,156,477,89 and crashing costs of Rp. 8,983,188,341.84. Analysis of human resources, obtained a total wage of Rp.508.880.304 workers and obtained a total of 4084.6 people. APD (Self Protection Equipment) and APK (Work Protection Equipment) which used by workers, was identified the risk of each work carried out while the project is being implemented. Communication in a project is very important to do to achieve maximum project results and minimize errors in project work.